The Time Preference of Chinese Tend to be Less Affected by Positive Emotions: As Proved by an Experimental Study - Yingnan, Shi; Li, Xinghao (Journal of Economics and Behavioral Studies, 2017)
This paper aims at testing whether positive emotions have a different impact on Chinese participants’ time preference choices from American respondents on average, considering that the Chinese people own a different culture background and more inward-oriented national characteristic. The researcher conducted a controlled experiment based on random assignments, and the experiment is specifically adapted for Chinese participants. Further, in order to approach to a more accurate result, the research also determines such effect is influenced, if any, by personality factors such as risk preference. The BDM (Becker-DeGroot-Marschak) and an MPL（Multiple Price List）methods were utilized to gather sufficient data and to ensure accurate measures. This paper indicates that, on average, for a Chinese participant, positive emotion will still reduce their time preference over intertemporal decision regarding to cash payment, but in a smaller amount on average, compared to an American respondent. Also, the result shows that, risk preference does play a role and tend to risk neutral persons have a weaker time-preference, compared to risk-takers and risk-avoiders. Moreover, several other factors, such as the health state, family income, and gender may also have correlation with time preferences. Alternative explanations are proposed at the end. This research may contribute to explain the differences of credit card usages preferences between the Chinese and American consumers and to explicate the reasoning of the Chinese economic miracles in the recent decades.